2018
DOI: 10.1186/s12864-018-5108-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing specific molecular biomarkers for thermal stress in salmonids

Abstract: BackgroundPacific salmon (Oncorhynchus spp.) serve as good biological indicators of the breadth of climate warming effects on fish because their anadromous life cycle exposes them to environmental challenges in both marine and freshwater environments. Our study sought to mine the extensive functional genomic studies in fishes to identify robust thermally-responsive biomarkers that could monitor molecular physiological signatures of chronic thermal stress in fish using non-lethal sampling of gill tissue.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
117
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(145 citation statements)
references
References 99 publications
11
117
0
Order By: Relevance
“…Proteins identified as part of the cellular stress response included up regulation of HSPs, a common indicator of stress related to abiotic and biotic factors in fish and other organisms (Basu et al, 2002;Huth & Place, 2016). We also identified several cytochrome proteins involved in oxidative and metabolic processes, and associated with thermal stress responses in salmon (Akbarzadeh et al, 2018). SEPRH, FKBP, and RAS related proteins have also been previously identified as significantly expressed in marine fish under stress (Chen et al, 2018;Evans & Somero, 2009;.…”
Section: Discussionmentioning
confidence: 81%
“…Proteins identified as part of the cellular stress response included up regulation of HSPs, a common indicator of stress related to abiotic and biotic factors in fish and other organisms (Basu et al, 2002;Huth & Place, 2016). We also identified several cytochrome proteins involved in oxidative and metabolic processes, and associated with thermal stress responses in salmon (Akbarzadeh et al, 2018). SEPRH, FKBP, and RAS related proteins have also been previously identified as significantly expressed in marine fish under stress (Chen et al, 2018;Evans & Somero, 2009;.…”
Section: Discussionmentioning
confidence: 81%
“…Our results showed that five of the 10 upregulated genes at 18, including two paralogs of SERPINH and two paralogs of hsp90a and hsp70, were heat shock proteins. These genes are known to be the most frequent heat shock proteins (HSPs) in response to higher temperature across salmonids and other species studied (Akbarzadeh et al, 2018a). The importance of molecular chaperoning of macromolecules during higher temperature has been well established.…”
Section: Temperature Biomarkersmentioning
confidence: 99%
“…In particular, the heat shock response (HSR), defined as the ability of the HSPs to re-fold thermally damaged proteins and prevent their cytotoxic aggregation, is a well-described phenomenon across taxa (Logan and Buckley, 2015). The upregulation of many paralogs relating to HSP genes including SERPIN, HSP70, and HSP90a were also observed in adult Sockeye salmon in response to chronic elevated temperature (Akbarzadeh et al, 2018a;Jeffries et al, 2012;Jeffries et al, 2014b). Our literature review revealed that the above HSP genes are upregulated in more than 16 different fish species belonging to different taxa, including salmonids in response to high temperature (Akbarzadeh et al, 2018a).…”
Section: Temperature Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations